Pengetahuan Gizi dan Riwayat Pola Makan Ibu Hamil Berhubungan dengan Kejadian Stunting pada Balita - Lestari, Kustati Budi (JURNAL KEPERAWATAN RAFLESIA, 2023)
Stunting is a global problem including Indonesia and a threat to developing countries related to the impact of malnutrition, malnutrition and infection on children, so this problem is urgent to be addressed. This study aims to analyze the relationship between nutritional knowledge and dietary history of pregnant women with the incidence of Stunting cases. The cross-sectional correlation design study used the purposive sampling method for as many as 53 respondents, based on the guidance of the results of height measurements 6 months earlier in the MCH book and researchers measured height and weight together with nurses/midwives during Posyandu activities in the month of data collection. The research was conducted for 1 month in the working area of the Puskesmas Tanah Tinggi Kota Tangerang. Data were collected using maternal nutrition knowledge questionnaires and dietary history of pregnant women developed by researchers with reliability results of 0.935 and 0.912. The results of the chi-square statistical test, show that low nutritional knowledge in pregnant women can trigger six times the incidence of Stunting with p: 0.002 and poor diet of pregnant women contributes seven times the incidence of Stunting with p: 0.003. Stunting is triggered by low maternal knowledge about nutrition and poor diet during pregnancy. Providing education related to nutrition for pregnant women and diet is better given before pregnancy, especially for adolescent girls or couples before marriage by utilizing adolescent posyandu.